Level of Success Practice of Occupational Safety Risk Management in Implementation of the Suramadu Bridge Inspection and Planning Project - Moch Rica; Ronny Durrotun Nasihien (Journal of World Conference (JWC), 2022)
The Suramadu Bridge Inspection and Planning Project is a construction management consulting project with a high risk of work in planning. In response, a study was conducted that aims to measure the success of the implementation of construction safety management to identify weaknesses in operational performance on the Suramadu Bridge Inspection and Planning project. This study uses an interview method through a questionnaire sheet to the stakeholders involved based on the Regulation of the Minister of Public Works and Public Housing Number 10 of 2021. The data obtained is then processed using SPSS software with a scoring method. Based on the results obtained in this study, it can conclude that the successful implementation of the Construction Safety Management System (SMKK) in the Implementation of the Suramadu Bridge Inspection and Planning Project reached a value of 83.73%, with the level of achievement classified in the Good category. In contrast, the dominant factor influencing the implementation of SMKK is construction safety planning which has the highest level of achievement of 86.88%. However, what needs more attention is the evaluation of construction safety performance with an achievement rate of 80.00%.